FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH BSI MOBILE - Samiudin, Askal (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2024)
This research was conducted with the aim of examining the impact of E-SERVQUAL variables on the level of satisfaction of BSI Mobile users in the Special Region of Yogyakarta Province. The method applied used the E-SERVQUAL model with the addition of responsiveness as a differentiating factor. The population of focus in this study consisted of active BSI Mobile users in 2022, totaling 82,244, while a sample of 200 BSI Mobile users scattered across the Special Region of Yogyakarta Province was selected. The approach used was quantitative descriptive, and the analysis was carried out using the SEM (structural equation model) method with the software SmartPLS 3.0.The research results indicate that reliability, fulfillment, and responsiveness have a significant impact on the level of satisfaction of BSI Mobile users. On the other hand, efficiency and security/privacy do not have a significant impact on the satisfaction of BSI Mobile users. The theoretical implications of this research are an enhancement of our understanding of the factors influencing the satisfaction of BSI Mobile users, especially in the context of Mobile banking services, from an academic perspective. On the practical side, the findings of this research can be considered in formulating BSI Mobile marketing policies.Keywords: E-Servqual; Cotumer Satisfaction; BSI Mobile